dentification of Benzoxazolinone Derivatives Based Inhibitors for Depression and Pain Related Disorders Using Human Serotonin and Norepinephrine Transporter as Dual Therapeutic Target: A Computational Approach - Selvaraj Manikandan; AR.Saranya; Thirugnanasambandam Ramanathan; Krishnan Selvarajan Kesavanarayanan; Teh LK; Salleh MZ (International Journal of Drug Delivery, 2014)
Pain is commonly associated with depression. Both pain and depression share common biological pathways and neurotransmitters, which has implications for the treatment of both disorders. A drug that could ameliorate both pain and depression could be beneficial in the development of new therapeutics in the management of disorders associated with pain/depression dyad. Alterations in the neurotransmitters namely, serotonin and norepinephrine in the central nervous system (CNS) have been implicated in the pathophysiology of pain and depression. Serotonin and norepinephrine reuptake inhibitors (SNRIs) have been implicated as a novel therapeutic target for a wide range of biological functions, including pain, anxiety and depression. 2-benzoxazolinone (2-BOA) from the mangrove Acanthus ilicifolius and its derivatives have been reported for its analgesic and antidepressant activities. In the present work, docking studies were done on the crystal structure of human transporters of serotonin (hSERT) and on homology modeled human transporters of norepinephrine (hNET) as therapeutic targets of depression and pain related disorders using 2-BOA and its derivatives as potential candidates. A homology model for hNET was constructed using MODELLER and validated. Further docking studies were done on hSERT and hNET using 2-BOA and its structural analogs. The result of the study proposes the possible potential candidate among 2-BOA derivatives that may be further developed as a therapeutic lead compound for use in disorders associated with depression and pain.